Case report: Ultrasound-guided percutaneous drainage combined with lavage using urokinase: An economical and effective treatment for muscular hematomas in hemophiliacs - Liu, Hao; Xu, Cong; Wang, Weizhen; Chen, Bin; Sun, Jing; Feng, Xiaoqin; Zhang, Yaru; Ma, Fei; Du, Lingli; Gao, Yang; Li, Yingjia (Frontiers in Surgery, 2023)
This was an initial effort to treat hemophiliac hematoma by ultrasound-guided intratumoral drainage and lavage with urokinase after adequate supplementation of coagulation factors. Two patients with severe hemophilia underwent ultrasound-guided percutaneous drainage in combination with lavage using urokinase. After 5-day and 3-day treatments, respectively, intramuscular hematomas in both patients disappeared, compression symptom was relieved, and no obvious adverse reactions or serious complications were observed during the treatment or follow-up. These findings suggest that ultrasound-guided drainage combined with lavage using urokinase is an immediate, safe, effective, and minimally invasive treatment for intramuscular hematomas in hemophiliacs, avoiding potential complications by surgical resection with relatively low treatment cost.